The protestant factor in Р. Hindenburg’s victory in the German presidential elections of 1925 - N. F. Virt (Гуманитарные и юридические исследования)
The article deals with the influence of the Protestant community of the Weimar Republic on the presidential elections of 1925. The use of religious contradictions within German society to mobilize the electorate in support of P. Hindenburg’s candidacy is analyzed. The religious aspect of elections is especially relevant in the study of state-confessional relations in Germany in the 1920s and understanding the degree of influence of religion on politics.The reasons and features of the formation of preelection inter-party coalitions are revealed. The role of the religious factor in the creation of the «Imperial block» is noted. Changes in the electoral base of candidates after the first round of elections are analyzed. The differences in political sympathies in the industrial and agrarian regions of Germany, as well as the contradictions in the ranks of the Bavarian People’s Party under the influence of the religious factor, are explained. The participation of the Protestant clergy in the election campaign in support of the candidate from the nationalist forces is characterized. The influence of the nomination from the coalition of the SPD and the Center Party of the Catholic V. Marx on the election results is indicated. A significant part of the Protestant clergy and Protestant organizations came out in support of P. Hindenburg. Campaigning for a Protestant candidate from church pulpits led to the mobilization of the conservative religious electorate and further victory of P. Hindenburg in the second round of the presidential elections in 1925.